Speciation and spectrophotometric determination of uranium in seawater - KONSTANTINOU, M.; PASHALIDIS, I. (Mediterranean Marine Science, 2004)
A series of ion-exchange and extraction procedures for the separation of uranium from seawater samples and subsequent spectrophotometric determination of uranium in seawater by means of arsenazo(III) is described. According to the measurements performed by means of traced samples at every stage of separation, the yield of the pre-analytical procedures is generally over 90% and the separation of uranium very selective. The mean uranium concentration in seawater samples collected from five different coastal areas in Cyprus was found to be 3.2 ± 0.2 & micro; g L-1. Uranium in seawater is stable in its hexavalent oxidation state and UO2 (CO3)34- is the predominant species under normal coastal conditions (pH ≥ 8, EH ≥ 0.35 mV, 1 atm and 0.03% CO2).